Pengaruh Kualitas Pelayanan dan Kepuasan Terhadap Loyalitas - Ridho Murjoko; Muchsin Saggaff Shihab (Program Studi Magister Manajemen FE Unsri, 2011)
The research aims to find out the impact of service quality and satisfaction on loyalty. Five dimensions of service quality i.e. issue program, academic reputation, physical aspect, career opportunity, contact personnel, responsiveness, and communication were analyzed. This research is descriptive – quantitative in nature. Data were obtained by using questionnaire which was distributed to the students of SMK Negeri 11, Jakarta. Using proportionate stratified random sampling technique, total sample of 87 respondents were obtained. Data were examined using both descriptive and statistical analysis. Results indicated physical aspect, responsiveness, and communication had the influence on the student satisfaction, meanwhile contact personnel, responsiveness, communication, and satisfaction had the effect on loyalty. Physical aspect had an indirect influence on student loyalty. It is suggested that the management pay more attention to program, academic reputation, career opportunity, and contact personnel. There is also a need for more research to answer which physical aspect is the most dominant.Keywords: service quality, satisfaction and loyalty